2013
DOI: 10.1523/jneurosci.3449-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Improves Neural Coding Efficiency Despite Increasing Correlations in Variability

Abstract: Exposure of cortical cells to sustained sensory stimuli results in changes in the neuronal response function. This phenomenon, known as adaptation, is a common feature across sensory modalities. Here, we quantified the functional effect of adaptation on the ensemble activity of cortical neurons in the rat whisker-barrel system. A multishank array of electrodes was used to allow simultaneous sampling of neuronal activity. We characterized the response of neurons to sinusoidal whisker vibrations of varying ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 69 publications
16
111
0
Order By: Relevance
“…Specifically, the total amount of noise in a neuronal ensemble can be described by the covariance matrix that includes both individual and interneuronal, correlated, variability [113]. Interneuronal variability is commonly referred to as 'noise correlation' and its impact on neuronal information processing has been studied extensively in a plethora of processes such as stimulus drive [114], neuronal adaptation [115,116], perceptual discrimination [117], attention [108,[118][119][120], perceptual and associative learning [121,122] and behavioural context [123]. In these studies, correlations were shown to be detrimental, beneficial or not relevant to the efficiency of population codes, depending on their structure and magnitude.…”
Section: (E) Local Field Potentials and Perceptual Awarenessmentioning
confidence: 99%
“…Specifically, the total amount of noise in a neuronal ensemble can be described by the covariance matrix that includes both individual and interneuronal, correlated, variability [113]. Interneuronal variability is commonly referred to as 'noise correlation' and its impact on neuronal information processing has been studied extensively in a plethora of processes such as stimulus drive [114], neuronal adaptation [115,116], perceptual discrimination [117], attention [108,[118][119][120], perceptual and associative learning [121,122] and behavioural context [123]. In these studies, correlations were shown to be detrimental, beneficial or not relevant to the efficiency of population codes, depending on their structure and magnitude.…”
Section: (E) Local Field Potentials and Perceptual Awarenessmentioning
confidence: 99%
“…In particular, they can facilitate or impair population coding, depending on the spatial structure of the noise correlations and the relationship between them and the encoded signal (Abbott and Dayan 1999;Josic et al 2009;Sompolinsky et al 2001). Adaptation to repeated stimulation reduces both single-neuron variability and pairwise noise correlations in sensory cortex (Adibi et al 2013;Gutnisky and Dragoi 2008). In specific cases this has promoted improved population-based stimulus estimation (Gutnisky and Dragoi 2008) and discrimination (Wang et al 2011).…”
Section: Adaptation and Population Codingmentioning
confidence: 99%
“…The temporal correlation between the spike trains of pairs of neurons is an important signature of network function. Spiking correlations are modulated by attention, stimulus tuning and presentation, learning, behavioral context, and sensory adaptation (Adibi et al 2013;Gutnisky and Dragoi 2008;Wang et al 2011;Cohen and Kohn 2011). While specific arrangements of correlated activity across a population of neurons can benefit cortical representation (Abbott and Dayan 1999;Averbeck et al 2006), in many cases widespread and unstructured correlations are deleterious to coding (Josic et al 2009;Sompolinsky et al 2001).…”
mentioning
confidence: 99%
“…Repeated whisker deflections have long been known to reduce neuronal responsivity in barrel cortex (for example [46]), but recently it has been found that this adaptation is also capable of increasing responsivity [47]. This enhanced responsivity has been attributed to inhibition being weakened more than excitation by adaptation ([48], but see [49]).…”
Section: Introductionmentioning
confidence: 99%